Improvement in pH and Total Iron Concentration of Acid Mine Drainage after Backfilling: A Case Study of an Underground Abandoned Mine in Japan - Kohei Yamaguchi (MDPI AG, 2021)
If the excavated underground veins are not backfilled, they may be a factor in the continued outflow of acid mine drainage (AMD). The flow rate of AMD can be reduced by backfilling underground drifts from abandoned mines. In addition, the quality of AMD may be improved as the flow rate of AMD reduces. In this paper, the quality of the AMD after backfilling was evaluated by a three-dimensional geochemical analysis model when the groundwater level was recovered after backfilling. The measured dissolved iron (Fe) and sulfate ion (SO42−) concentrations and pH before backfilling the drift were reproduced by the calibration of the simulation. Using the calibrated model, the pH at the outlet of the drift was changed from about pH 3 before backfilling to about pH 4 to 5 after backfilling. When calcite was contained in the filling materials of the drift, the pH approached neutral. However, when gypsum was formed, the neutralization was inhibited. The Fe concentration discharged from the drift was calculated at approximately 0.002 mol/L before backfilling. The total Fe concentration was calculated at 0.0004 mol/L or less after backfilling, and the dissolved Fe concentration decreased by several orders of magnitude after backfilling. A geochemical model quantitatively evaluated the improvement in water quality after backfilling the drifts. This method can be applied to the other abandoned mines with similar hydrogeological conditions.